Comparison of Strain-Encoding and Feature-Tracking Derived Myocardial Deformation Assessment of Left Ventricular Function in a Pediatric and Adult Congenital Heart Disease Cohort - Chew, Joshua D.; George-Durrett, Kristen; Acheampong, Benjamin; Weiner, Jeffrey G.; Slaughter, James C.; Parra, David A.; Soslow, Jonathan H. (Pediatric cardiology, 2022)
Background Cardiac magnetic resonance (CMR) strain can be assessed with feature-tracking (FT), which utilizes a post-processing algorithm to quantify myocardial deformation on routine cine images, and strain-encoding magnetic resonance imaging (SENC), which uses parallel magnetization tags combined with out-of-plane phase-encoding gradients to quantify deformation. Assessing agreement is critical to determine whether results can be translated between methods. We compared SENC to FT in the assessment of left ventricle (LV) global longitudinal strain (GLS) and global circumferential strain (GCS) in a cohort of pediatric and adult congenital heart disease (ACHD) patients. Methods Pediatric subjects and ACHD patients underwent CMR on 1.5 T Siemens scanners, including balanced steady-state-free precession (bSSFP) cine imaging and SENC acquisitions in apical two and four chamber, left ventricular outflow tract, and short axis views. bSSFP cine imaging FT analysis was completed with Medis QStrain. Myocardial Solutions MyoStrain was used to analyze SENC. Correlation was assessed by Spearman’s rank correlation coefficient. Agreement between techniques was assessed with concordance correlation coefficient (CCC) and Bland–Altman. Results The cohort included 134 patients, 75 with congenital heart disease (56%). The median age was 16.3 years (IQR 13.7, 19.5). Median LV ejection fraction was 57% (IQR 54.4, 61.6). SENC and FT were in poor agreement for GLS (Spearman’s ρ = 0.58, p < 0.001; CCC 0.24) and GCS (Spearman’s ρ = 0.29, p < 0.001; CCC 0.03). Conclusion There was poor agreement between SENC and FT derived GLS and GCS in a cohort of pediatric and ACHD patients, suggesting that SENC and FT cannot be used interchangeably.